2020
DOI: 10.1136/annrheumdis-2020-218009
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies related to systemic autoimmune rheumatic diseases in severely ill patients with COVID-19

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research. Patient consent for publication Not required.Provenance and peer review Not commissioned; externally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 8 publications
11
157
0
6
Order By: Relevance
“…With respect to baseline clinical characteristics, the investigated cohort is comparable to previous reports ( 2 , 19 ). Our result of autoantibodies in patients with severe COVD-19 is in line with first results from other groups ( 10 , 11 , 20 ); however, we are the first to put this observation into context with clinical, imaging, and histopathology findings. Furthermore, we confirm the association between higher age, male sex, and elevated LDH with severe course of COVID-19 in line with literature data ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to baseline clinical characteristics, the investigated cohort is comparable to previous reports ( 2 , 19 ). Our result of autoantibodies in patients with severe COVD-19 is in line with first results from other groups ( 10 , 11 , 20 ); however, we are the first to put this observation into context with clinical, imaging, and histopathology findings. Furthermore, we confirm the association between higher age, male sex, and elevated LDH with severe course of COVID-19 in line with literature data ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our data sustained that autoimmunity is linked to SARS-CoV-2 infection, since none of the patients had a previous autoimmune disease. This is in accordance with what has recently been described in the literature concerning the onset of autoimmune diseases upon COVID-19 infection11 .…”
supporting
confidence: 93%
“…Different autoantibodies are not only disease markers but can be also pathogenic, therefore transferring autoantibodies or performing transfusions with neutralizing antibodies might not be the best choice for these patients 11 .…”
Section: Accepted Articlementioning
confidence: 99%
“…This finding suggests a post-SARS-CoV-2 or para-SARS-CoV-2 infectious autoimmune reactivation. The authors suggested that the presentation of cytokines, such as IL-6, in the cytokine storm, can lead to autoinflammatory activation and autoimmunity, probably through natural B-cells or molecular mimicry ( Vlachoyiannopoulos et al, 2020 ). Tocilizumab is being used in patients with COVID-19, mostly in the advanced disease stage, on the basis of the previous experience with chimeric antigen receptor (CAR) T-cell immunotherapy-induced cytokine release syndrome ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%